BET bromodomain-containing epigenetic reader proteins regulate vascular smooth muscle cell proliferation and neointima formation. Issue 3 (30th April 2020) - Dutzmann, Jochen; Haertlé, Marco; Daniel, Jan-Marcus; Kloss, Frederik; Musmann, Robert-Jonathan; Kalies, Katrin; Knöpp, Kai; Pilowski, Claudia; Sirisko, Mirja; Sieweke, Jan-Thorben; Bauersachs, Johann; Sedding, Daniel G; et al.
Abstract: Aims: Recent studies revealed that the bromodomain and extra-terminal (BET) epigenetic reader proteins resemble key regulators in the underlying pathophysiology of cancer, diabetes, or cardiovascular disease. However, whether they also regulate vascular remodelling processes by direct effects on vascular cells is unknown. In this study, we investigated the effects of the BET proteins on human smooth muscle cell (SMC) function in vitro and neointima formation in response to vascular injury in vivo . Methods and results: Selective inhibition of BETs by the small molecule (+)-JQ1 dose-dependently reduced proliferation and migration of SMCs without apoptotic or toxic effects. Flow cytometric analysis revealed a cell cycle arrest in the G0/G1 phase in the presence of (+)-JQ1. Microarray- and pathway analyses revealed a substantial transcriptional regulation of gene sets controlled by the Forkhead box O (FOXO1)1-transcription factor. Silencing of the most significantly regulated FOXO1-dependent gene, CDKN1A, abolished the antiproliferative effects. Immunohistochemical colocalization, co-immunoprecipitation, and promoter-binding ELISA assay data confirmed that the BET protein BRD4 directly binds to FOXO1 and regulates FOXO1 transactivational capacity. In vivo, local application of (+)-JQ1 significantly attenuated SMC proliferation and neointimal lesion formation following wire-induced injury of the femoral artery in C57BL/6 mice. Conclusion: Inhibition of the BET-containing protein BRD4 after vascular injury by (+)-JQ1 restores FOXO1 transactivational activity, subsequent CDKN1A expression, cell cycle arrest and thus prevents SMC proliferation in vitro and neointima formation in vivo . Inhibition of BET epigenetic reader proteins might thus represent a promising therapeutic strategy to prevent adverse vascular remodelling.